The antioxidant and antimicrobial capacities of phenolic profiles of some Salvia L. Seeds grown in Turkey - Emre, Irfan; Kursat, Murat; Kirbag, Sevda; Erecevit, Pinar; Emre, Mustafa Yunus; Yilmaz, Okkes; Civelek, Semsettin (Pamukkale University, 2021)
The aim of current study is to show phenolics, antioxidant capacities and antimicrobial activities of seeds of five Salvia L. (S. frigida Boiss., S. candidissima subsp. candidissima Vahl., S. virgata Jacq., S. verticillata L. var. verticillata and S. russellii Benth.) taxa grown in Turkey. The flavonoid and phenolic acid contents were measured by using HPLC whilst the antioxidant capacities were determined by using different methods. In addition, agar well diffusion method was used to determine the antimicrobial activities of Salvia species in this study. It was found that S. frigida, S. verticillata var. verticillata and S. russellii have the highest catechin contents and S. frigida and S. verticillata var. verticillata have high rosmarinic acid while S. frigida, S. candidissima subsp. candidissima and S. verticillata var. verticillata have high vanilic acid. Also, it was determined that S. frigida and S. verticillata var. verticillata have high DPPH radical scavenging activities in 150 and 250 µL while S. frigida and S. verticillata var. verticillata have highest ABTS radical scavenging activity in all concentrations apart from 25 µL for S. frigida. Furthermore, S. frigida and S. verticillata var. verticillata have high total phenolic contents. On the other hand, Salvia species have similar lipid peroxidation inhibitions. However, the metal chelating activities of Salvia species are different. And also, it was demonstrated that Salvia taxa have antimicrobial activity. © IJSM 2021
Keywords: Antimicrobial activity; Antioxidant capacity; Flavonoids; Phenolic acids; Salvia L